Penggantian tepung kacang merah dan tepung lele dalam semprong: dampak terhadap daya terima, kandungan gizi, dan nilai ekonomi sebagai makanan tambahan balita - Calvin Ramadhani; Annis Catur Adi (Jurnal SAGO Gizi dan Kesehatan, 2023)
Background: The incidence of stunting in toddlers can have a negative impact on the growth and development of toddlers in the future. The direct cause of stunting is inadequate food intake. There is a need for food formulations with high protein and calcium content in an effort to overcome stunting.Objectives: This research aims to analyze the effect of the substitution of local food ingredients, namely red beans and catfish, on the acceptability, nutritional content, and economic value of semprong as an alternative food supplement for toddlers.Methods: The type of research in formula development is true experimental with a completely randomized design. There are 3 (three) types of treatment (F0, F1, F2). The research sample was taken randomly or with random sampling. The analyzers used were 25 untrained panelists. Data collection uses a preference test questionnaire (hedonic). Data analysis used the Friedman and Wilcoxon test. Protein and calcium content were obtained from calculations and laboratory tests. The research was conducted at Posyandu Mawar, from February to May 2023.Results: The results of the research showed that there were significant differences in color (p= 0,007), aroma (p= 0,030), and texture (p= 0,04). However, there was no significant difference in taste characteristics (p = 0,050). From the results of the ranking of acceptability, nutritional content and economic value, the best formula was obtained F2 (7,79% substitution of red bean flour and 7,79% catfish flour). The nutritional content per 100 g of F2 formula meets protein and calcium requirements of at least 10% per day for toddlers. The economic value of the best formula is IDR 10,366 per 50 g.Conclusion: Semprong cake substitution of red bean flour and catfish flour can be recommended as an alternative food supplement for toddlers